Optimization of Stunting Prevention and Treatment Through Local Food Utilization - Yunita Satya Pratiwi (Future Science, 2023)
Background: Stunting is a condition of failure to thrive in children which is characterized by a lower height than the standard height at a certain age due to chronic malnutrition. Objective: Analyze the incidence of stunting in Indonesia, the government's strategy for overcoming stunting through local food, to analyze the obstacles, advantages, and products resulting from research on the use of local food. Method: Systematic Literature Review (SLR) with PRISMA guidelines from 2017 to 2023, a total of 42 articles out of 104 articles. Results and Discussion: The prevalence of stunting in Indonesia in 2022 will decrease by 21.6%. The government's efforts to reduce the incidence of stunting are included in the strategy starting from the SDGs, RPJMN 2020- 2024, RAN-PASTI 2021-2024, to RAN-PG 2020-2024. One of the obstacles to the use of local food, namely low acceptance, while the benefits can increase the family economy. Research products to prevent and overcome stunting, such as corn milk, TORI meatballs, shredded catfish, and purple sweet potato cake. Conclusion: The prevalence of stunting in Indonesia in 2022 is still relatively high. Currently, the government is using the strategy contained in the RAN-PG by utilizing local food and improving nutrition services. The need for support from various cross-sectors is assisted by the use of technology so that stunting reduction can be implemented. Products resulting from research on the use of local food have emerged, ranging from heavy to light meals (snacks).